A tactical role for reverse auctions: A market maker perspective - Standing, Susan; Standing, Craig; Love, Peter (2009)
Electronic marketplaces have been used for procurement in various industries by both small and large organisations.However, the role of electronic marketplaces in procurement is still unclear and strategies and organisational implications of trading via an e-marketplace are not well defined.An electronic marketplace facilitates transactions between buyers and sellers and a common transaction mechanism for price negotiation is an electronic auction. This paper investigates the role of reverse auctions in procurement including the organisational implications and strategies for using an electronic auction.We use a case study (Revnet) of an electronic auction provider to analyse their role and benefits. The findings show that e-auctions can be used as part of a strategic procurement strategy to reduce procurement costs and improve efficiency and are more likely to be used for non-critical business for products and services that do not require strong ties with suppliers.The success of e-auctions within this context relies to a large extent on the quality of contract specifications. The narrower tactical role for e-auctions that is now emerging in some organisations is shaped by the fear and disdain surrounding their use in the past and in particular the perception of the damage to supplier relationships that their widespread adoption in procurement can create.